PERBANDINGAN HARGA SAHAM PERUSAHAAN FARMASI BUMN SEBELUM DAN SESUDAH PENGEMBANGAN VAKSIN VIRUS CORONA (COVID-19) - Welley, Morenly Marchel; Oroh, Franky N. S; Walangitan, Mac Donald (FEB Universitas Sam Ratulangi Manado, 2020)
ABSTRACT: The existence of an extraordinary event that occurred, namely the Covid-19 Pandemic, caused the global and national economies to experience obstacles. Not only does it have an impact on the economy, but this also has an impact on the capital market. The President's announcement regarding the development of the Covid-19 vaccine provides hope for the economy and capital market to revive. The state-owned pharmaceutical company appointed by the government has also benefited from vaccine development. The purpose of this study was to determine the difference in the share price of BUMN Pharmaceutical Companies before and after the development of the corona virus vaccine (Covid-19). The data analysis technique used in this study was the Paired sample t-test. The results showed that (1) the stock price of KAEF before the announcement of vaccine development and the stock price of KAEF after the announcement of vaccine development was a significant difference and (2) the stock price of INAF before the announcement of vaccine development and the stock price of INAF after the announcement of vaccine development had a significant difference.